Data Refrensi Pola Berjalan Orang Indonesia pada Kecepatan Rendah, Sedang dan Tinggi di Atas Treadmill - Robin Novriansyah; Agus Priambodo; Bagaskara Yogatama; Marijo Marijo (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: Gait analysis is the study about how to move. However, the normal gait reference which is currently used is the normal gait of Europeans. The body proportions, leg length, and height between Europeans and Indonesians are different.Methods: The samples were 44 Indonesian aged 18 – 26 years which was divided into 22 males and 22 females. Samples used legging and socks that had been marked with a color at a certain point. The research sample walked on a treadmill at low, medium and high speeds and recorded from the back and sides. Based on the video, the angles of the hip joint, knee join was assessed.Results: In male subjects, the joint angles of low, medium and high speed walking: maximal thigh joint (21.30o, 21.77o, 22.67o), minimal thigh joint (-7.05o, -7.74o, 8.66o), maximal knee joint (55.25o, 57.00o, 60.04o), minimal knee joints (9.63o, 10.13o, 10.50o). In female subjects, the joint angles of low, medium and high speed walking: maximal thigh joint (24.02o, 24.43o, 24.99o), minimum thigh joint (-3.25o, -3.86o, -4.22o), maximal knee joint (53.60o, 56.80o, 58.99o), minimal knee joints (11.12o, 12.94o, 12.83o).Conclusion: The faster walking speed, the greater angle of thigh joint and knee joint